Trimethylchitosan hydrochloride obtained from lobster carapace chitin on a bench scale - Rodriguez-Chanfrau, Jorge Enrique [UNESP]; Rodriguez-Riera, Zalua; Gamiotea-Turro, Daylin [UNESP] (Biointerface Research Applied Chemistry, 2019)
Starting from the chitin obtained from the lobster carapace, chitosan was obtained. This polymer, due to its high biodegradability, biocompatibility and mucoadhesivity, has a wide use in the pharmaceutical and food industry. Currently, it has great importance in the development of biomaterials for the regeneration of bone and cartilaginous tissues. However, its applications are limited by the insolubility at pH greater than 6. To increase its solubility, different methodologies have been reported. The intensive methylation of the chitosan has been one of the methodologies that have been studied in the last years, generating the N,N,N-trimethylchitosan. This molecule has the characteristic of having permanent positive charges in the chain as a consequence of the quaternization of the amino groups present in the structure of chitosan. Previous studies showed the influence of the agitation rate and the reaction time on the methylation process of the chitosan, using as an alkylating agent the dimethyl sulfate. This allowed to establish a technological process to transform the chitosan. The aim of this work was to obtain N,N,N-trimethylchitosan chloride from chitosan obtained chitin from lobster carapace bench scale. Infrared spectroscopy, Energy dispersive X-ray spectrometry, Nuclear Magnetic Resonance and Intrinsic viscosity were used to characterize the product obtained. The results of the analysis by Infrared spectroscopy, Energy dispersive X-ray spectrometry and Nuclear Magnetic Resonance showed that the methylation process of the chitosan proposed in this work was effective to obtain the desired product. The degree of quaternization, degree of dimethylation and degree of acetylation were 49.2%, 57.5% and 13.3%, respectively. While the value of the intrinsic viscosity [eta] of the sample was 78.5 cm(3)/g. The results corroborate the possibility of modifying chitosan by applying the methodology proposed in this work.
Keywords: Chitosan; N,N,N-trimethylchitosan hydrochloride; Chitosan trimethylation process; Degree of quaternization